2012
DOI: 10.1007/s13181-012-0276-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive Outcome After Intentional Overdose of Dabigatran

Abstract: This case shows the clinical course of a patient with an acute, massive dabigatran overdose with no significant clinical consequences. Currently, there is no ideal method to monitor anticoagulation levels; there is no pharmacologic reversal method, and hemodialysis is an undesirable treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
1
26
1
2
Order By: Relevance
“…In another case report, a 57-year-old woman with a medical history of depression and atrial fibrillation had taken 11.25 g of dabigatran in a suicide attempt [4] . Despite an ecchymosis indicative of prior trauma, there was no evidence of acute bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In another case report, a 57-year-old woman with a medical history of depression and atrial fibrillation had taken 11.25 g of dabigatran in a suicide attempt [4] . Despite an ecchymosis indicative of prior trauma, there was no evidence of acute bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…86 Moreover, a recent case report involving an intentional overdose of dabigatran involved gastric lavage as recommended by a national guidance and administration of activated charcoal. 87,88 In this case, no blood products or factor concentrates were administered, and the patient did not undergo hemodialysis. 88 Despite marked prolongations of baseline TT, the patient did not manifest any signs of overt bleeding and survived the overdose.…”
Section: Clinical Trials and Case Reports On Active Drug Removalmentioning
confidence: 99%
“…87,88 In this case, no blood products or factor concentrates were administered, and the patient did not undergo hemodialysis. 88 Despite marked prolongations of baseline TT, the patient did not manifest any signs of overt bleeding and survived the overdose. It is important to note that because of its action in the gut, activated charcoal is likely only to be a useful therapy if used within 1 to 2 hours of a dose (or overdose) of dabigatran.…”
Section: Clinical Trials and Case Reports On Active Drug Removalmentioning
confidence: 99%
“…[12][13][14] In cases of overdose in patients who took their last NOAC dose within two hours to four hours prior, oral activated charcoal may attenuate absorption of the drug. [15][16][17][18] Nonspecific hemostatic factors that have been studied as potential NOAC reversal agents include prothrombic complex concentrates (PCCs), activated PCCs, recombinant activated factor VII (rFVIIa), and fresh frozen plasma. PCCs are the preferred nonspecific hemostatic agent for NOAC reversal; they are plasma-derived products that contain three (factors II, IX, and X) or four (factors II, IX, X, and VII) clotting factors, in addition to variable amounts of heparin and the natural coagulation inhibitors protein C and protein S. Animal studies have demonstrated that PPCs have a variable ability to normalize anticoagulation parameters and to prevent or attenuate bleeding seen with NOAC usage.…”
Section: General Supportive Measuresmentioning
confidence: 99%